Minimax conditions for Schatten ideals of compact operators - Formisano, Teresa; Kissin, Edward (Eurasian Mathematical Journal, 2012)
In this paper we study the validity of various types of minimax condition for operators in Schatten ideals of compact operators on separable Hilbert spaces.